Engaging the diaspora in an era of transnationalism - Changzoo Song (IZA World of Labor, 2014)
Since the 1990s, South Korea's population has been aging and its fertility rate has fallen. At the same time, the number of Koreans living abroad has risen considerably. These trends threaten to diminish South Korea's international and economic stature. To mitigate the negative effects of these new challenges, South Korea has begun to engage the seven million Koreans living abroad, transforming the diaspora into a positive force for long-term development.
Keywords: O19; O38; O53; 330; South Korea; diaspora; development; diaspora engagement policy; extraterritorial nation